The Analysis of Consumptive Behavior in Students of The Faculty of Economics and Business Makassar State University - Wardhana Haeruddin, Muhammad Ilham; Muis, Mahlia; Ismail, Muhammad; Pono, Maat (PT. Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of lifestyle and self-concept on consumptive behavior in students of the Faculty of Economics, Makassar State University. The population in this study were 2757 students of the Faculty of Economics, Makassar State University and a sample of 96 students was drawn. This study uses a type of quantitative research with a regression approach. Data collection techniques were carried out by observation, interviews, documentation and distributing questionnaires (questionnaires). The analysis technique used is multiple linear regression. The results showed that partially, the lifestyle variable (X1) had a positive effect on consumptive behavior (Y) with a value of T count (5.732) > T table (1.985) and the self-concept variable (X2) had a positive effect on consumptive behavior (Y) with a value of T count (3.085) > T table (1.985), while simultaneously the lifestyle variable (X1) and self-concept (X2) had a positive effect on consumptive behavior (Y) with a value of F count (51.087) > F table (3.10).